Commodity Funds How To Fix Them? - Cohen, Daniel (OECD Publishing, 2007)
Poor countries are and will remain for some time vulnerable to external shocks, whether to export prices or from natural disasters. The lowest-income countries have a higher incidence of shocks than other developing countries and tend to suffer larger damages when shocks occur. For the poorest countries, the average number of disasters between 1997 and 2001 has been one every 2.5 years. Commodity price shocks are also more severe for poor countries. Low-income countries experience this type of shock on average every 3.3 years. About 26 highly-indebted countries have an export concentration of more than 50 per cent in three or fewer commodities, while 62 per cent of the total exports of the least developed countries are unprocessed primary commodities. Exogenous shocks on commodity prices have significant direct adverse effects on growth and the multiplier effects of negative terms of trade shocks can also be large. Collier and Sewn (2001) show, for a sample of cases where the direct income loss averaged 6.8 per cent of GDP, the total correlated loss of income amounted to about twice that much, to 14 per cent of GDP. Research shows that these negative shocks increase the incidence of poverty. The shocks also have a significant impact on fiscal and external balances. An IMF study shows that terms-of-trade shocks and adverse weather conditions have played an important role in exacerbating debt problems3
Keywords: Development